On inequalities for norms of intermediate derivatives on a finite interval - Babenko, V. F.; Kofanov, V. A.; Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For functionsf which have an absolute continuous (n−1)th derivative on the interval [0, 1], it is proved that, in the case ofn>4, the inequality \| f^(n - 2) \|_∞ 4^n - 2 (n - 1) ! \| f \|_∞ + \| f^(n) \|_∞ /2 holds with the exact constant 4 n−2(n−1)!.